PROPOSAL OF A MONITORING MODULE FOR THE USE OF RENEWABLE ENERGIES IN HIGH ANDEAN HOUSING - Quispe Santivañez, Grimaldo Wilfredo (2023)
The research focused on developing a module capable of evaluating the performance of renewable energy in spaces within a solar-powered house. To achieve this, an Arduino Uno microcontroller was used to enable the connection of sensors and the Bluetooth communication interface. Similarly, the mobile application generation platform APP INVENTOR was used to create an application that allows synchronization between an Android cell phone and the Arduino module via Bluetooth. This application has an interface and a sequence of commands that allow the user to monitor in real time the temperatures of up to 8 spaces within the house. The study arose with the purpose of evaluating the energy efficiency of an ecological house located in a high-altitude area in the city of Tarma. The house was built with ecological materials and uses thermal insulation methods in walls, a radiant floor system and electricity supply through photovoltaic panels. The ultimate goal is to be able to replicate this type of housing in other high-altitude areas in the country and possibly abroad.